Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s10295-010-0769-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and structural characterization of hydroxamate siderophore produced by marine Vibrio harveyi

Abstract: In the present study, 22 different bacteria were isolated from open ocean water from the Gulf of Mannar, India. Of the 22 isolates, 4 were identified as Vibrio spp. (VM1, VM2, VM3 and VM4) and found to produce siderophores (iron-binding chelators) under iron-limited conditions. Different media were found to have an influence on siderophore production. Maximum siderophore production was observed with VM1 isolate in MM9 salts medium at 48 h of incubation. The isolate was confirmed as Vibrio harveyi based on 16S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…4-I), this result was consonance with a previous study (Clark et al, 2014), that indicated the predominate of catecholate type siderophores in the Bacillus genus, specifically Bacillibactin catecolate type siderophores. However, in the study of (Murugappan et al, 2011) they reported that its impossible to characterize the siderophores based on the bacteria species, because siderophores of varying nature have been produced by the same genus. In the same test for the siderophore of Aspergillus niger MH603592, its show maximum absorbance at 450 which is confirmed the hydroxymate nature of siderophores (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4-I), this result was consonance with a previous study (Clark et al, 2014), that indicated the predominate of catecholate type siderophores in the Bacillus genus, specifically Bacillibactin catecolate type siderophores. However, in the study of (Murugappan et al, 2011) they reported that its impossible to characterize the siderophores based on the bacteria species, because siderophores of varying nature have been produced by the same genus. In the same test for the siderophore of Aspergillus niger MH603592, its show maximum absorbance at 450 which is confirmed the hydroxymate nature of siderophores (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial isolates were grown for 3 days on Iron-restricted minimal salt medium (MM9) at 37ºC (Murugappan et al, 2011), while the isolated fungi were grown for 14 days on PDA medium at 28º C (Srivastava et al, 2013). The culture supernatant of both types of microbiota was further subjected to Chrome Azurol Sulfonate liquid assay, for quantitative assessment of siderophore production.…”
Section: -Siderophores Production Estimationmentioning
confidence: 99%
“…Thus, it is likely that these genes have spread among the various bacterial strains by horizontal transmission. A strain of Vibrio harveyi isolated from the open ocean of the Gulf of Mannar produced a dihydroxamate siderophore (86). However, its complete structure has not been determined.…”
Section: Transport Of Iron Complexesmentioning
confidence: 99%
“…Further 16S rRNA gene sequencing was carried out for species identification. Amplification of the 16S rRNA gene was attempted by PCR using forward primer 5 0 -AGAGTTTGATCCTGGTC AG-3 0 and reverse primer 5 0 -TAAGGAGGTGATCCAG GC-3 0 [9]. The 16S rRNA gene sequence of the isolate was submitted to NCBI and compared with related gene sequences.…”
Section: Strain Isolation and Identificationmentioning
confidence: 99%
“…For siderophore production, one ml of the isolate (5 9 10 7 bacterial cells/ml) was suspended in iron depleted minimal (MM9) medium [9]. After incubation, the cell free supernatant (10,000 rpm for 15 min) was examined for siderophore production by FeCl 3 test and CAS agar plate method [11].…”
Section: Screening For Siderophore Productionmentioning
confidence: 99%